Prática de leitura, produção de textos e análise linguística em aulas de língua portuguesa : possibilidades didáticas a partir do trabalho com o gênero carta do leitor - Sá, Juliane Nogueira de (2016)
In this research, we developed a teaching sequence with a focus on gender reader's letter and applied it in a high school class in a public school located in the municipality of Serra/ES, in order to combine the practice of reading, text production and linguistic analysis. There are some aims of this research: to contribute to the studies on teaching sequences in working with reading, text production and linguistic analysis in mother tongue in Basic education in Brazil apply the didactic sequence in the research participant group; analyze the results of the teaching sequence, through the textual productions of students and their daily activities in the classroom. We selected some authors to theoretically substantiate our research. They are: Bakhtin (2003), Antunes (2003), Marcuschi (2008) Dolz and Schneuwly (2004), Geraldi (2004), Martelotta (2008), Bezerra (2007) Suassuna (2012). The methodology of this research is to carry out an action research in a public school in the municipality of Serra/ES, in order to understand better the process that involves, more specifically, the practice of textual production in the classroom. After observing the chosen class, we apply the teaching sequence with the aim of encouraging, priority, the practice of reading and textual production. For this, we use the gender reader’s letter to be a genre that is available to students in newspapers and magazines and develops in students the ability of criticism and reflection of varied themes. The results of this research are presented by means of comparison between the first productions of the students and their final productions, becoming interpretative analysis of the two versions. Episodes of classroom occurred during the implementation of the teaching sequence are also analyzed.